In Vitro Evaluation of the Antifungal Activity of Ghassoul-Based Formulations with Oregano and Thyme Essential Oils against Penicillium sp. - Hamid Ziyat; Mohammed Naciri Bennani; Safae Allaoui; Jamal Houssaini; Hasna Nait M’barek; Soukaina Arif; Hassan Hajjaj (Journal of Chemistry)
The essential oils from aromatic plants are today considered a suitable tool to protect stored grains from fungal attacks. The purpose of this work is to study the effect of formulations of thyme and oregano essential oil (EO) adsorbed on purified (Gh-P) and sulfuric acid-activated (Gh-A) ghassoul on the biological activity of fungal pathogens. Purified and activated ghassoul were characterized by XRD and FTIR, and EOs used in this study were issued from two medicinal plants known in Morocco and commercially available. Their chemical compositions were analyzed by the GC-MS technique. The main constituents of thyme EO were thymol (67.13%), ρ-cymene (4.85%), Z-caryophyllene (1.77%), and γ-terpinene (2.74%). Oregano EO contained carvacrol (59.82%), γ-terpinene (10.85%), and α-pinene (9.89%). This work focused on the study of the antifungal activity of EOs mixed with purified and sulfuric acid-activated ghassoul, in order to look for new natural bioactive products and assess their antifungal activity. Penicillium sp. was used as a pathogen agent for biological activity on Czapek agar medium. The results showed that the active ghassoul formulations had significant antifungal activity against Penicillium sp. Gh-A-thyme, Gh-A-thymol, and Gh-A-oregano had an inhibitory potential of more than 75% and excelled to retain it over time even after five months. On the other hand, the three purified ghassoul formulations (Gh-P-thyme, Gh-P-thymol, and Gh-P-oregano) showed an initial inhibitory power of less than 22%, which was decreasing over time.